2017
DOI: 10.1111/bjd.15800
|View full text |Cite
|
Sign up to set email alerts
|

Serological diagnostics in the detection of IgG autoantibodies against human collagen VII in epidermolysis bullosa acquisita: a multicentre analysis

Abstract: The two commercially available ELISA systems allow for a highly sensitive and specific diagnosis of EBA. The sensitivity of the Col7-NC1/NC2 ELISA is significantly higher compared with the ELISA based on the Col7-NC1 domain only.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
28
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 47 publications
3
28
0
4
Order By: Relevance
“…Preparation and evaluation of immunofluorescence microscopy on salt-split human skin was performed as previously described. 27…”
Section: Indirect Immunofluorescence Microscopy With Salt-split Normamentioning
confidence: 99%
See 1 more Smart Citation
“…Preparation and evaluation of immunofluorescence microscopy on salt-split human skin was performed as previously described. 27…”
Section: Indirect Immunofluorescence Microscopy With Salt-split Normamentioning
confidence: 99%
“…IgG serum autoantibodies against BP180, BP230 and ColVII were excluded using commercially available ELISA (Euroimmun, L€ ubeck, Germany); according to the manufacturers' protocol. 27 Presence of autoantibodies against laminin 332 were excluded by ELISA using native human laminin 332 as previously described. 28…”
Section: Exclusion Of Other Circulating Autoantibodiesmentioning
confidence: 99%
“…The sensitivity of IIF microscopy on human salt-split skin for the detection of anti-BMZ autoantibodies in EBA ranged between 27% and 100% in several studies, with a pooled measure of 75.9% in 426 EBA sera reported so far. [4]…”
Section: Indirect Immunofluorescencementioning
confidence: 99%
“…concluded that type VII collagen combined NC1/NC2 domains ELISA is superior to ELISA based on type VII collagen NC1 domain only, immunoblotting, and IIF on salt-split skin, with a sensitivity of 97.9%. [4] All of the immunoassays above are restricted to several specialized laboratories across the world.…”
Section: Indirect Immunofluorescencementioning
confidence: 99%
“…5 Other causes of mucosal erosions and ulcerations include other AIBD, such as laminin c-1 pemphigoid and epidermolysis bullosa acquisita, Stevens-Johnson syndrome, erythema multiforme and erosive lichen planus (LP). 6,7 Of note, cases of oral MMP with clinical and histopathological characteristics of oral LP have been highlighted recently. 8 Moreover, coexistence of lichenoid mucositis with acantholysis is typically found in paraneoplastic pemphigus.…”
mentioning
confidence: 99%